Intergenerational Communication Across The Life Span - Williams, Angie; Nussbaum, Jon F. (London: Lawrence Erlbaum Associates Publishers, 2001)
The volume employs the perspective that the understanding of human behavior across the life span is enhanced by studying communicative behavior in inter generational interaction.
Includes Bibliographic References and Index.
Keywords: Inter generational Communication--Intergenerational Relations--Communication in the family--Conflict of generations